Strategies to Strengthen Group Cohesion, Stress Management, Self-Awareness and Creativity to Improve Teacher Work Effectiveness: A Study in Tasikmalaya Regency - Evi Fitriyanti; Eka Suhardi; Rita Retnowati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study investigates the influence of group cohesion, stress management, self-awareness, and creativity on the work effectiveness of elementary school teachers in Tasikmalaya Regency. Employing an exploratory sequential mixed-methods design, the research integrates qualitative and quantitative approaches. The qualitative phase involved in-depth interviews and observations, while the quantitative phase collected data from 163 proportionally randomized ASN (Aparatur Sipil Negara) teachers through structured questionnaires. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS), complemented by the System Improvement Through Organizational Renewal and Empowerment (SITOREM) method to prioritize development indicators. The findings reveal that group cohesion, stress management, and self-awareness significantly and positively influence teacher creativity, which in turn mediates their impact on work effectiveness. Among the variables, self-awareness emerges as the strongest direct predictor of work effectiveness, whereas group cohesion exerts the most substantial influence on enhancing creativity. Creativity serves as a crucial mediating factor, bridging psychosocial factors and overall teacher performance. These results underscore the importance of fostering a collaborative work culture, implementing effective stress management initiatives, promoting self-reflective practices, and cultivating creative pedagogical approaches. This research contributes to the body of knowledge on teacher development by integrating psychosocial and professional dimensions into a comprehensive framework. The study offers valuable insights for policymakers and school leaders in advancing educational transformation in alignment with the vision of a Golden Indonesia 2045.